A study on the level of job satisfaction among workers in EPF, Seremban / Noor Zaininah Md.Zin - Md.Zin, Noor Zaininah (Faculty of Business Management, 2001)
Individual's satisfaction in their workplace is related to their fulfillment of their basic needs. The more the needs are satisfied, the greater the degrees of a person's job satisfaction. Workers' satisfaction is among the important elements required in delivering quality services to the users. The aim of this study is to determine the workers' satisfaction levels in relations to various basic needs to ensure the quality of work performance. The study determines workers' satisfaction levels in relation to their basic needs and to suggest ways to motivate the workers. A survey using structured questionnaires was administrated to the staff in EPF for data collection. All the data was analyzed by using the Statistical Package for Social Sciences (SPSS) version 10.0. The study reveals that the satisfaction levels of the workers are different from one department to another. The percentage of satisfaction level in term of physiological needs is 61 percent, security needs 70 percent, social and belonging needs 42 percent, esteem needs 42 percent and self-actualization needs 47 percent. It shows that management of EPF is quite successful in fulfill the basic needs of the workers. In term to improve the quality of the work performance, the workers' satisfaction must be enhanced through several ways (see recommendation). The management of EPF should act to satisfy their workers in order to ensure a good work performance. It is hoped that the result from this study will help to increase the efficiency of management of EPF in satisfying their workers basic needs.